SAT0475 ECHINOCOCCOSIS AND AUTO-IMMUNE INFLAMMATORY ARTHRITIS; REPORT OF 8 CASES AND REVIEW OF THE LITERATURE. (June 2019) - Zufferey, Pascal; Camille, Zambaz; Muller, Rudiger; Noémie, Boillat-Blanco; Huegle, Thomas; Paul, Hasler; Villiger, Peter
Abstract : Background: The prevalence of Echinococcosis in Western Europe and Switzerland has been rising in the past 20 years: >30 cases per year have been reported since 2005 (1). A few case reports (2) and some experimental animal studies (3) have suggested that the immunosuppression linked to inflammatory arthritis and their treatments could favor the development and the growth of parasitic lesions. On the other hand, a recent French study (4) has a shown that the prevalence of Echinococcosis in arthritis patients was close to the normal population. The characteristics of the parasitic disease were quite similar whether inflammatory arthritis was present or not Objectives: To evaluate the yearly recent incidence of this disease among patients with inflammatory arthritis in Switzerland and to search for any interaction between arthritis, the treatment of arthritis and development and evolution of the echinococcosis. Methods: We collected all the cases with the diagnosis of echinococcosis among the patients regularly followed and treated for inflammatory arthritis in three different tertiary rheumatology centers of Westen Switzerland (1.7 million inhabitants, 5000 arthritis pts). Results: Between 2012 and 2018, 8 cases of echinococcosis (1.3 case/year/5000pts) could be found. The estimated yearly incidence among this arthritis population appears therefore to be significantly higher (p<0.0001) than the one reported in the general population in Switzerland (30/8000000 inhabitants). Figure summarized the relation between the parasitic and the inflammatory disease. Different types of inflammatory arthritis were implicated. Previous and ongoing arthritis treatments comprised also different types of biologics. In 6/8 cases, the parasitic disease was asymptomatic and limited to a single organ, a proportion much higher than what is usually found in the general population. In 2 of them, the discovery was very close in time to the diagnosis of arthritis and treatment initiation (<6 months). 4 pts could be treated by surgery alone. 6 continued their treatments for arthritis. No evidence of relapses after surgery (4 pts) or progression under albendazole (4 pts, median follow-up: 44 months) was found. Conclusion: The incidence of echinococcosis in autoimmune arthritis appears to be higher than in general population but remains very low. Outcome seems not to be affected by inflammatory arthritis and their treatments but the long-time effects of the combination between arthritis treatments and albendazole need to be further evaluated. References: 1:. Vuiton DA, et al. :Veterinary parasitology (2013), 110-20 2:. Weiner SMet al; Rheumatol Int (2011), 1399–1400 [3] : Armuda-Fernandez MT, et al.; Parasitology (2016), 1252–1260. [4] : Gauchet A, et al.; Clinical Infectious Diseases (2014), 1095–104 Disclosure of Interests: Pascal Zufferey: None declared, Zambaz camille: None declared, Rudiger Muller: None declared, Boillat-Blanco Noémie: None declared, Thomas Huegle Grant/research support from: AbbVie, Lilly, Novartis and Pfizer, Speakers bureau: AbbVie, Lilly, Novartis and Pfizer, Hasler paul: None declared, Peter Villiger: None declared